Analisis Kinerja Bongkar Muat Curah Kering di Pelabuhan Tanjung Tembaga : Studi Kasus : Pt Delta Artha Bahari Nusantara - Ilma Nur Fadhila Aghnia; Dian Junita Arisusanty; Anak Agung Istri Sri Wahyuni; Jose Beno (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
This research focuses on analyzing the performance of dry bulk unloading at Tanjung Tembaga Port, with a case study of PT Delta Artha Bahari Nusantara. The main objective of this research is to evaluate the performance of dry bulk loading and unloading services at the port and identify efforts that can be made to improve loading and unloading productivity. The research method used is descriptive quantitative, with data collection through direct observation, interviews, and documentation studies. The data obtained were analyzed using statistical methods and compared with the established operational service performance standards. The results showed that the performance of loading and unloading at Tanjung Copper Port seen from all indicators of loading and unloading performance can be concluded that the average of all indicators includes good category as evidenced by the total percentage of the average of 79.96%. This study concludes that to improve loading and unloading performance, PT Delta Artha Bahari Nusantara needs to improve facilities and infrastructure, improve operational systems, and provide training to the workforce. Thus, it is expected that the port can be more efficient in handling dry bulk loading and unloading and contribute positively to the supply and distribution chain.